Method for improving activity of fluorgypsum and fluorgypsum product
By mixing fluorine gypsum powder, water and calcium oxide, and adding sodium molybdate dihydrate, the hydration process of fluorine gypsum is changed, and high-strength fluorine gypsum products are generated, which solves the problems of poor hydration activity and environmental pollution of fluorine gypsum, and realizes the Resource utilization of fluorine gypsum.
Patent Information
- Application Number
- CN202411219134.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-03
AI Technical Summary
The hydration activity of fluorine gypsum is poor, it is difficult to achieve resource utilization, and accumulation is prone to environmental pollution.
Mix fluorine gypsum powder, water and calcium oxide and add sodium molybdate dihydrate to form a fluorine gypsum slurry and cure it in a constant temperature and humidity environment to change the transformation process of anhydrous gypsum to dihydrate gypsum to form a tightly interwoven prism-like prism-like Dihydrate gypsum improves its physical strength.
The hydration rate and mechanical properties of fluorine gypsum are significantly improved, making it possible to use it to replace natural gypsum production gypsum board, realizing the recycling of fluorine gypsum and avoiding environmental pollution.
Smart Images

Figure CN119241104A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a method for improving the activity of fluorgypsum and a fluorgypsum product. Background Art
[0002] Fluorogypsum is an industrial byproduct produced during the production of hydrogen fluoride and other fluorine-containing chemicals. Due to its large production volume, high difficulty in processing, and potential harm to the environment, the treatment and utilization of fluorogypsum has become an important research topic in the field of environmental protection and resource utilization. Fluorogypsum is mainly composed of anhydrous calcium sulfate and a small amount of fluoride, usually in powder or block form. Its composition is complex and contains a certain amount of harmful substances, such as fluoride. Improper treatment will cause harm to the environment and human health. The stacking of large amounts of fluorogypsum occupies land resources and may cause soil and water pollution. The fluoride it contains will seep into groundwater and affect the surrounding ecological environment. In addition, fluorogypsum is easily weathered during the stacking process, forming dust pollution, further aggravating environmental problems.
[0003] Although fluorinated gypsum has abundant calcium resources, its hydration activity is poor. If it is used directly as a building material, the mechanical properties of the fluorinated gypsum products obtained after hydration are poor. It cannot replace natural gypsum in the production of gypsum boards, and it is difficult to achieve the recycling of fluorinated gypsum.
[0004] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention
[0005] The object of the present invention is to provide a method for improving the activity of fluorgypsum and a fluorgypsum product, so as to help solve or improve the problems in the prior art that fluorgypsum has poor hydration activity, it is difficult to realize resource utilization of fluorgypsum, and fluorgypsum accumulation easily causes environmental pollution.
[0006] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: a method for improving the activity of fluorgypsum, comprising the following steps: (1) mixing fluorgypsum powder, water and calcium oxide evenly to obtain fluorgypsum slurry; (2) adding sodium molybdate dihydrate to the fluorgypsum slurry, mixing evenly to obtain fluorgypsum slurry; (3) curing the fluorgypsum slurry to obtain a fluorgypsum product.
[0007] Preferably, in step (1), the mass ratio of the fluorslurry powder to calcium oxide is (96-104):(0.5-1.5), and the mass ratio of water to the fluorslurry powder is (0.29-0.33):1; in step (2), the mass ratio of sodium molybdate dihydrate to the fluorslurry powder is 0.06%-1.5%.
[0008] Preferably, in step (2), the mass ratio of sodium molybdate dihydrate to fluorsulphite powder is 0.3%-1.1%.
[0009] Preferably, after obtaining the fluorgypsum slurry, it is allowed to stand for 5-10 minutes before adding the sodium molybdate dihydrate.
[0010] Preferably, the fluorgypsum powder is obtained by drying and grinding fluorgypsum, and the fluorgypsum powder can pass through a 30-mesh sieve.
[0011] Preferably, the drying temperature is 45-60° C., and the drying time is 10-24 h.
[0012] Preferably, step (3) comprises: A. molding the fluorgypsum slurry in a mold and demolding the fluorgypsum slurry; B. continuing to cure the fluorgypsum slurry after demolding to obtain the fluorgypsum product.
[0013] Preferably, in step A, the fluorinated gypsum slurry is placed in a mold, compacted, and vibrated on a vibration table. After the fluorinated gypsum slurry is initially set, a plastic wrap is applied, and the mold is removed after curing for 10-24 hours.
[0014] Preferably, the curing in step A and / or B is carried out in a constant temperature and humidity environment, with a temperature of 17-25° C. and a humidity of 60%-70% RH.
[0015] The present invention also provides a fluorinated gypsum product, which adopts the following technical solution: a fluorinated gypsum product, wherein the fluorinated gypsum product is prepared by the method as described above.
[0016] Beneficial effects:
[0017] The method for improving the activity of fluorinated gypsum of the present invention helps to solve the problems that fluorinated gypsum is difficult to hydrate and utilize and easily causes environmental pollution due to its accumulation, so that fluorinated gypsum can be used as a building material and the recycling of fluorinated gypsum solid waste resources can be realized.
[0018] The method for improving the activity of fluorgypsum of the present invention comprises adding sodium molybdate dihydrate after the acidity of fluorgypsum is neutralized, thereby changing the gypsum crystal form of fluorgypsum during the transformation process from anhydrous gypsum to dihydrate gypsum (so that dispersed, granular anhydrous gypsum is hydrated to form tightly interwoven prismatic dihydrate gypsum); sodium molybdate dihydrate has weak alkalinity after being dissolved in water, and can play a certain modification role. At the same time, sodium molybdate dihydrate reacts with fluorgypsum components to generate insoluble calcium molybdate, making its surface structure more compact and improving the physical strength of fluorgypsum products.
[0019] The fluorinated gypsum product of the present invention has good mechanical properties (when the dosage of sodium molybdate dihydrate is 0.3%-1.1% of the fluorinated gypsum powder, the 28d compressive strength of the fluorinated gypsum product can reach above 38MPa), has no frosting phenomenon, and can replace natural gypsum for producing gypsum boards. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:
[0021] Figure 1 It is a top view of the test block of the fluorgypsum product of Example 5 of the present invention after being demoulded and cured for 7 days;
[0022] Figure 2 This is a left view of the test block of the fluorinated gypsum product of Example 5 of the present invention after being cured for 7 days after demoulding;
[0023] Figure 3 This is a comparison chart of the flexural strength of fluorinated gypsum products at various ages in Examples 1-11 of the present invention;
[0024] Figure 4 This is a comparison chart of the compressive strength of fluorinated gypsum products at various ages in Examples 1-11 of the present invention;
[0025] Figure 5 This is a comparison chart of the flexural strength of fluorinated gypsum products of various ages in Example 5 of the present invention and Comparative Examples 1-6;
[0026] Figure 6 This is a comparison chart of the compressive strength of fluorinated gypsum products of various ages in Example 5 of the present invention and Comparative Examples 1-6;
[0027] Figure 7 The XRD spectrum of the fluorinated gypsum product of Comparative Example 1 after curing for 7 days;
[0028] Figure 8 The XRD spectrum of the fluorinated gypsum product of Comparative Example 2 after curing for 7 days;
[0029] Fig. 9 This is the XRD spectrum of the fluorinated gypsum product of Example 5 of the present invention after curing for 7 days;
[0030] Fig.10 This is the SEM image of the fluorinated gypsum product of Comparative Example 1 after curing for 7 days;
[0031] Fig.11 This is the SEM image of the fluorinated gypsum product of Comparative Example 2 after curing for 7 days;
[0032] Fig.12 This is the SEM image of the fluorinated gypsum product of Example 5 of the present invention after curing for 7 days. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0034] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0035] Fluorogypsum is hard gypsum, that is, type II anhydrous gypsum. Its "hardness" is reflected in its slow hydration process and extremely low hydration rate. Therefore, the help of an activator is needed to promote the hydration process of fluorogypsum. "Improving activity" means promoting the hydration reaction of fluorogypsum and stimulating activity, which is mainly reflected by the early and late strengths of the samples obtained after curing. Without stimulating the activity of fluorogypsum, after mixing fluorogypsum powder with water to obtain slurry, the sample failed to solidify after being formed and cured in a constant temperature and humidity environment for 3 days. After curing for 7 days, the sample still had no flexural and compressive strength (hydration was extremely slow).
[0036] The present invention provides a method for improving the activity of fluorgypsum in view of at least one of the problems of poor hydration activity of fluorgypsum, slow rate of generating dihydrate gypsum crystals, difficulty in realizing resource utilization of fluorgypsum and easy environmental pollution caused by accumulation of fluorgypsum.
[0037] The method for improving the activity of fluorgypsum in this embodiment comprises the following steps: (1) mixing fluorgypsum powder, water and calcium oxide evenly (adjusting the pH value of fluorgypsum) to obtain fluorgypsum slurry; (2) adding sodium molybdate dihydrate to the fluorgypsum slurry and mixing evenly to obtain fluorgypsum pure slurry; (3) curing the fluorgypsum pure slurry to obtain a fluorgypsum product.
[0038] The present invention first adds calcium oxide to fluorgypsum powder, and then adds sodium molybdate dihydrate (calcium oxide and sodium molybdate dihydrate are not added at the same time, because adding them at the same time will cause calcium oxide and sodium molybdate dihydrate to react, which greatly reduces the modification and excitation effects of the two). Calcium oxide can neutralize the acidity of fluorgypsum and create an environment with high alkaline activity; sodium molybdate dihydrate helps to change the crystal form of fluorgypsum during the transformation process from anhydrous gypsum to dihydrate gypsum. Sodium molybdate dihydrate has weak alkalinity after being dissolved in water (molybdate dihydrate Sodium is a weak acid and strong base salt. The pH of 5% sodium molybdate dihydrate aqueous solution is about 9.0-10.0. It can play a certain role in modification. At the same time, part of sodium molybdate dihydrate can react with fluorgypsum components to form insoluble calcium molybdate, making its surface structure more compact, promoting the hydration reaction of fluorgypsum, shortening the time required for the hydration reaction of fluorgypsum, accelerating the crystallization of dihydrate gypsum, and improving the strength of fluorgypsum hardened body (sodium molybdate dihydrate is a salt activator. When added to the surface of fluorgypsum, it can generate unstable complex salt (mCaSO 4 ·nH 2 O), accelerate the formation of fluorgypsum supersaturation and reduce its crystallization activation energy, accelerate crystallization, and significantly improve the hydration rate; the double salt is decomposed into dihydrate gypsum and hydrated salts in the presence of water and activator, and the dihydrate gypsum is continuously crystallized, so that the slurry forms a tightly interwoven crystal structure and shortens the setting time).
[0039] Specifically, in step (1), a small portion of the fluorgypsum in the fluorgypsum slurry is converted from anhydrous gypsum to dihydrate gypsum, but the effect is not obvious; during the curing process in step (3), the fluorgypsum continues to react, and eventually most of the fluorgypsum is converted into dihydrate gypsum, which is reflected in the significant improvement of the early and late strengths of the fluorgypsum products obtained after curing.
[0040] In a preferred embodiment of the method for improving the activity of fluorgypsum of the present invention, in step (1), the mass ratio of water to fluorgypsum powder is (0.29-0.33):1 (for example, 0.29:1, 0.3:1, 0.31:1, 0.32:1 or 0.33:1, etc.); the pH of the fluorgypsum slurry is 10.8-11.2 (for example, 10.8, 10.9, 11.0, 11.1 or 11.2); in step (2), the mass ratio of sodium molybdate dihydrate to fluorgypsum powder is 0.06%-1.5% (for example, 0.06%, 0.08%, 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, 1.2% or 1.5%). Among them, if the dosage of sodium molybdate dihydrate is too large, it will have an adverse effect on the mechanical properties of fluorgypsum products; if the dosage of sodium molybdate dihydrate is too small, it will not be able to stimulate the activity of fluorgypsum well, and the improvement effect on the hydration reaction of fluorgypsum is limited; calcium oxide can play a role in adjusting the pH of fluorgypsum. If the dosage of calcium oxide is too small, the pH of the fluorgypsum slurry will be too low; if the dosage of calcium oxide is too large, it will lead to higher costs.
[0041] Preferably, the pH of fluorgypsum is 2.8, and the mass ratio of fluorgypsum powder and calcium oxide is (96-104):(0.5-1.5) (for example, 96:0.5, 96:1, 96:1.5, 104:0.5, 104:1, 104:1.5, 100:0.5, 100:0.8 or 100:1.5, etc.).
[0042] In a preferred embodiment of the method for improving the activity of fluorgypsum of the present invention, in step (2), the mass ratio of sodium molybdate dihydrate to fluorgypsum powder is 0.3%-1.1% (for example, 0.3%, 0.5%, 0.7%, 0.9% or 1.1%).
[0043] Preferably, in step (2), the mass ratio of sodium molybdate dihydrate to fluorgypsum powder is 0.7%; in this case, the 28d flexural strength of the fluorgypsum product can be increased by more than 30 times, and the 28d compressive strength can be increased by more than 10 times (relative to the case when calcium oxide and sodium molybdate dihydrate are not used to stimulate the activity of fluorgypsum).
[0044] In a preferred embodiment of the method for improving the activity of fluorgypsum of the present invention, after obtaining the fluorgypsum slurry, it is first allowed to stand for 5-10 minutes (for example, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes), and then sodium molybdate dihydrate is added. Among them, by standing for 5-10 minutes after mixing calcium oxide and fluorgypsum evenly to obtain fluorgypsum slurry, calcium oxide can fully neutralize the acidity of fluorgypsum, and then sodium molybdate dihydrate is added to promote the hydration of fluorgypsum, stimulate the activity to obtain dihydrate gypsum, and change the dihydrate gypsum crystal form. Fluorogypsum continues to be cured for about 3 days in a constant temperature and humidity environment to rapidly hydrate, and the hydration degree of fluorgypsum is greatly improved, thereby greatly improving the sample strength of the prepared fluorgypsum product. If the standing time after obtaining the fluorgypsum slurry is too short, the neutralization of calcium oxide (fluorgypsum) is insufficient; if the time is too long, the fluorgypsum slurry will solidify and harden, which is not conducive to subsequent stirring.
[0045] In a preferred embodiment of the method for improving the activity of fluorgypsum of the present invention, the fluorgypsum powder is obtained by heating, drying and grinding the fluorgypsum, and the fluorgypsum powder can pass through a 30-mesh sieve. Heating and drying the fluorgypsum not only helps to remove water attached to the surface of the fluorgypsum and prevent adhesion during grinding (adhesion is not conducive to the subsequent activation of the activity of the fluorgypsum), but also helps to discharge some impurities in the fluorgypsum in the form of gas.
[0046] In a preferred embodiment of the method for improving the activity of fluorgypsum of the present invention, the heating and drying temperature is 45-60°C (for example, 45°C, 48°C, 51°C, 54°C, 57°C or 60°C), and the drying time is 10-24h (for example, 10h, 14h, 18h, 21h or 24h).
[0047] In a preferred embodiment of the method for improving the activity of fluorgypsum of the present invention, step (3) comprises: A. forming the fluorgypsum slurry in a mold and demolding; B. continuing to cure after demolding to obtain a fluorgypsum product.
[0048] In a preferred embodiment of the method for improving the activity of fluorgypsum of the present invention, in step A, after the fluorgypsum slurry is placed in a mold, it is compacted and vibrated on a vibration table (for example, the vibration time may be 1.5-2 minutes; the vibration is to eliminate bubbles and voids), and after the fluorgypsum slurry is initially set, a plastic wrap is affixed, and the mold is removed after curing for 10-24 hours (for example, 10 hours, 13 hours, 16 hours, 19 hours, 22 hours or 24 hours); in step B, the curing time may be continued for 60-72 hours (for example, 60 hours, 63 hours, 66 hours, 69 hours or 72 hours).
[0049] In a preferred embodiment of the method for improving the activity of fluorgypsum of the present invention, the curing in step A and / or B is carried out under a constant temperature and humidity environment, with a temperature of 17-25°C (for example, 17°C, 19°C, 21°C, 23°C or 25°C) and a humidity of 60%-70% RH (for example, 60%, 62%, 64%, 66%, 68% or 70%).
[0050] The present invention also provides a fluorinated gypsum product, and the fluorinated gypsum product of the embodiment of the present invention is prepared by the method described above. For example, the fluorinated gypsum product can be a fluorinated gypsum board.
[0051] The method for improving the activity of fluorgypsum and the fluorgypsum product of the present invention are described in detail below through specific examples.
[0052] In the following examples: the fluorinated gypsum used in the present invention comes from Henan Duofuduo New Materials Co., Ltd., which is a byproduct of the reaction of fluorite and sulfuric acid to prepare hydrofluoric acid. The pH of the fluorinated gypsum is about 2.8, and the attached water content of the fluorinated gypsum before drying is greater than 2% (obtained by testing with a gypsum phase composition analyzer); the chemical composition of the fluorinated gypsum, by weight, includes: CaO34.70%, SO 3 62.75%、SiO 2 0.51%, Fe 2 O 3 0.14%, F - 0.31%, BaO 0.04% and other ingredients 1.55%; calcium oxide reagent comes from Hongyan Reagent Factory, Hedong District, Tianjin; sodium molybdate dihydrate reagent comes from Shanghai MacLean Biochemical Technology Co., Ltd. or Tianjin Zhonglian Chemical Reagent Co., Ltd.
[0053] Example 1
[0054] The method for improving the activity of fluorgypsum in this embodiment comprises the following steps:
[0055] (1) The fluorinated gypsum is heated and dried in an oven at 45° C. for 20 hours, and after heating and drying, it is ground in a ball mill for 3 minutes; then, it is sieved through a 30-mesh screen to remove larger particles, thereby obtaining fluorinated gypsum powder.
[0056] (2) 100 parts by weight of the fluorgypsum powder obtained in step (1), 1 part by weight of calcium oxide and water (the weight ratio of water to fluorgypsum powder is 0.31:1) are mixed, stirred sufficiently, and then allowed to stand for 5-10 minutes to obtain a fluorgypsum slurry (the pH of the fluorgypsum slurry is 10.9).
[0057] (3) adding sodium molybdate dihydrate (the amount of sodium molybdate dihydrate is 0.3% of the weight of fluorgypsum powder) to the fluorgypsum slurry obtained by the treatment in step (2) to activate the fluorgypsum to obtain a fluorgypsum clean slurry;
[0058] (4) Brush mineral oil on the mold, scoop the fluorinated gypsum slurry into the mold while slowly stirring, lift the front end of the mold by about 10 mm, and then let it fall, repeating this five times to eliminate bubbles; then, shape the fluorinated gypsum slurry in a 40 mm × 40 mm × 160 mm mold, vibrate on a vibration table for 2 min, and after initial setting, cover with plastic wrap and place in a standard curing room (constant temperature and humidity, 20°C, 65% RH humidity) for curing, and demold after 20 h; after demolding, continue to cure in the standard curing room for 3 days (i.e., 72 hours after demolding), 7 days and 28 days, respectively, to obtain fluorinated gypsum products of different ages of this embodiment.
[0059] Example 2
[0060] The difference between this embodiment and embodiment 1 is that in step (3), the amount of sodium molybdate dihydrate used is 0.4% by weight of fluorgypsum; the rest is consistent with embodiment 1.
[0061] Example 3
[0062] The difference between this embodiment and embodiment 1 is that in step (3), the amount of sodium molybdate dihydrate used is 0.5% by weight of fluorgypsum; the rest is consistent with embodiment 1.
[0063] Example 4
[0064] The difference between this embodiment and embodiment 1 is that in step (3), the amount of sodium molybdate dihydrate used is 0.6% by weight of fluorgypsum; the rest is consistent with embodiment 1.
[0065] Example 5
[0066] The difference between this embodiment and embodiment 1 is that in step (3), the amount of sodium molybdate dihydrate used is 0.7% by weight of fluorgypsum; the rest is consistent with embodiment 1.
[0067] Example 6
[0068] The difference between this embodiment and embodiment 1 is that in step (3), the amount of sodium molybdate dihydrate used is 0.8% by weight of fluorgypsum; the rest is consistent with embodiment 1.
[0069] Example 7
[0070] The difference between this embodiment and embodiment 1 is that in step (3), the amount of sodium molybdate dihydrate used is 0.9% by weight of fluorgypsum; the rest is consistent with embodiment 1.
[0071] Example 8
[0072] The difference between this embodiment and embodiment 1 is that in step (3), the amount of sodium molybdate dihydrate used is 1.0% by weight of fluorgypsum; the rest is consistent with embodiment 1.
[0073] Example 9
[0074] The difference between this embodiment and embodiment 1 is that in step (3), the amount of sodium molybdate dihydrate used is 1.1% by weight of fluorgypsum; the rest is consistent with embodiment 1.
[0075] Example 10
[0076] The difference between this embodiment and embodiment 1 is that in step (3), the amount of sodium molybdate dihydrate used is 0.06% by weight of fluorgypsum; the rest is consistent with embodiment 1.
[0077] Embodiment 11
[0078] The difference between this embodiment and embodiment 1 is that in step (3), the amount of sodium molybdate dihydrate used is 1.5% of the weight of fluorgypsum; the rest is consistent with embodiment 1.
[0079] Comparative Example 1
[0080] The method for improving the activity of fluorgypsum in this comparative example comprises the following steps:
[0081] (1) The fluorinated gypsum is heated and dried in an oven at 45° C. for 20 hours, and after heating and drying, it is ground in a ball mill for 3 minutes; then, it is sieved through a 30-mesh screen to remove larger particles, thereby obtaining fluorinated gypsum powder.
[0082] (2) 100 parts by weight of the fluorinated gypsum powder obtained in step (1) and water (the weight ratio of water to fluorinated gypsum powder is 0.31:1) are mixed, stirred thoroughly, and then allowed to stand for 5-10 minutes to obtain a fluorinated gypsum slurry (the pH of the fluorinated gypsum slurry is 2.8).
[0083] (3) Brush mineral oil on the mold, scoop the fluorinated gypsum slurry into the mold while slowly stirring, lift the front end of the mold by about 10 mm, and then let it fall, repeating this five times to eliminate bubbles; then, the fluorinated gypsum slurry is formed in a 40 mm × 40 mm × 160 mm mold, vibrated on a vibration table for 2 min, and after initial setting, covered with plastic wrap and placed in a standard curing room (constant temperature and humidity, 20° C., 65% RH humidity) for curing, and continued to be cured in the standard curing room for 3 d (72 h), 7 d and 28 d, respectively, to obtain fluorinated gypsum products of different ages of this comparative example.
[0084] Among them, because calcium oxide and sodium molybdate dihydrate were not used to modify and excite the fluorgypsum in this comparative example, the fluorgypsum slurry failed to coagulate and could not be demolded after 20 hours of curing in step (3), so the demolding was continued for 72 hours.
[0085] Comparative Example 2
[0086] The method for improving the activity of fluorgypsum in this comparative example comprises the following steps:
[0087] (1) The fluorinated gypsum is heated and dried in an oven at 45° C. for 20 hours, and after heating and drying, it is ground in a ball mill for 3 minutes; then, it is sieved through a 30-mesh screen to remove larger particles, thereby obtaining fluorinated gypsum powder.
[0088] (2) mixing 100 parts by weight of the fluorgypsum powder obtained in step (1), 1 part by weight of calcium oxide and water (the weight ratio of water to fluorgypsum powder is 0.31:1), stirring thoroughly and then standing for 5-10 minutes to obtain a fluorgypsum slurry (the pH of the fluorgypsum slurry is 10.9);
[0089] (3) Brush mineral oil on the mold, scoop the slurry into the mold while stirring slowly, lift the front end of the mold by about 10 mm, and then let it fall, repeating this five times to eliminate bubbles; then, shape the fluorinated gypsum slurry in a 40 mm × 40 mm × 160 mm mold, vibrate on a vibration table for 2 minutes, and after initial setting, cover with plastic wrap and place in a standard curing room (constant temperature and humidity, 20°C, 65% RH humidity) for curing, and demold after 20 hours; after demolding, continue to cure in the standard curing room for 3 days (72 hours), 7 days and 28 days to obtain fluorinated gypsum products of different ages of this comparative example.
[0090] Comparative Example 3
[0091] The difference between this comparative example and Example 5 is that the added calcium oxide is 0.6 parts by weight (the pH of the fluorgypsum slurry is 6.9); the rest is consistent with Example 5.
[0092] Comparative Example 4
[0093] The difference between this comparative example and Example 5 is that calcium oxide and sodium molybdate dihydrate are added simultaneously (the pH of the fluorgypsum slurry obtained after the simultaneous addition of calcium oxide and sodium molybdate dihydrate is 7.4); the rest is consistent with Example 5.
[0094] Comparative Example 5
[0095] The difference between this comparative example and Example 5 is that the dosage of sodium molybdate dihydrate is 2.0%; the rest is consistent with Example 5.
[0096] Comparative Example 6
[0097] The difference between this comparative example and Example 5 is that sodium oxalate (dosage is 0.7%) is used instead of sodium molybdate dihydrate; the rest is consistent with Example 5.
[0098] Experimental example
[0099] In the following experimental process: the water used in the analytical experiment is deionized water or distilled water (water used for pH determination), and the water used in the physical and mechanical properties test is clean urban domestic water. The test water volume is determined according to the method in GB / T17669.4-1999 "Determination of physical properties of building gypsum paste".
[0100] 1. After the fluorinated gypsum product of Example 5 was demoulded and cured for 7 days, photos were taken to observe:
[0101] from Figure 1 It can be seen that the surface of the fluorinated gypsum product of Example 5 has no frosting phenomenon and is smooth and beautiful. That is, the fluorinated gypsum product of Example 5 has significant early and late strength effects and no frosting phenomenon, overcoming the shortcomings of the products obtained by some activators, such as reduced late strength or surface frosting. Figure 2 It can be seen that the side of the fluorinated gypsum product of Example 5 has no cracks and pore defects and has a dense structure.
[0102] 2. Determination of strength:
[0103] Number of test blocks: At least three test blocks of each embodiment or comparative example should be kept (used as test samples of 3d, 7d and 28d fluorgypsum products respectively) for the determination of flexural strength. After the flexural strength determination, the two half-specimens obtained from each test block are used for the compressive strength determination, and the average of the two data is taken.
[0104] The 3d, 7d and 28d flexural strength and compressive strength of fluorgypsum products are measured according to the method in GB / T17669.3-1999 “Determination of Mechanical Properties of Building Gypsum”.
[0105] The 3d, 7d and 28d flexural and compressive strengths of the fluorinated gypsum products prepared in the above examples and comparative examples were tested, and the test results obtained are shown in Tables 1 and 2. Figure 3-6 shown.
[0106] Table 1 Flexural and compressive strength of fluorinated gypsum products in different embodiments and comparative examples
[0107]
[0108]
[0109] Table 2 Strength improvement of fluorinated gypsum products in Example 5 relative to the comparative example
[0110]
[0111] In Table 1 above, "3d flexural strength" and "3d compressive strength" refer to the strength of the fluorinated gypsum product obtained after curing in a constant temperature and humidity environment for 72 hours after demolding; the subsequent 7d and 28d strengths also refer to the strength of the fluorinated gypsum product obtained after curing in a constant temperature and humidity environment for 7d and 28d after demolding. In Table 2 above, "increase multiple" is calculated according to "compressive strength or flexural strength value of Example 5 / corresponding strength value of the control sample".
[0112] As can be seen from Table 1, the best physical strength effect is Example 5, that is, the optimal dosage of sodium molybdate dihydrate is 0.7%, and the mechanical properties of the early and late products are excellent; in Table 2, compared with Comparative Example 1, Example 5 has a 28d flexural strength increased by 32.5 times, and a 28d compressive strength increased by 10.5 times; compared with Comparative Example 2, Example 5 has a 3d flexural strength increased by 41 times, a 3d compressive strength increased by 5.1 times, a 7d flexural strength increased by 6.1 times, a 7d compressive strength increased by 2.3 times, a 28d flexural strength increased by 4.1 times, and a 28d compressive strength increased by 3.4 times, which shows that the effect of the activator (sodium molybdate dihydrate) is very Obviously; Example 5 is compared with Comparative Example 3, which shows that if the fluorgypsum slurry is not adjusted to a suitable pH, the strength of the fluorgypsum product will be poor; Example 5 is compared with Comparative Example 4, which shows that the simultaneous addition of calcium oxide and sodium molybdate dihydrate (when sodium molybdate dihydrate and calcium oxide are added at the same time, sodium molybdate dihydrate will react with calcium oxide) will greatly reduce the modification and excitation effects; Example 5 is compared with Comparative Example 5, which shows that excessive dosage of sodium molybdate dihydrate will be detrimental to the mechanical properties of the product; Example 5 is compared with Comparative Example 6, which shows that the excitation effect of sodium oxalate is poor, and the excitation effect of sodium molybdate dihydrate for 3d is better than that of sodium oxalate for 7d, which is almost equivalent to the excitation effect of sodium oxalate for 28d.
[0113] from Figure 3 and Figure 4It can be seen that the mechanical properties of the fluorinated gypsum product of Example 5 are the best, and the optimal dosage of sodium molybdate dihydrate is 0.7%. Figure 5 and Figure 6 It can be seen that the strength of Example 5 is significantly greater than that of other comparative examples at different ages, indicating that the proportion and method adopted in Example 5 have the most significant effect on improving the activity of fluorgypsum.
[0114] 3. X-ray diffraction: After the physical strength test of the test block (cured for 7 days after demolding), the broken pieces were dried in a vacuum drying oven at 45°C until constant weight was reached. The dried sample was ground and passed through a 200-mesh sieve to obtain a sample powder. X-ray diffraction (XRD) measurement was performed using a rotating target X-ray diffractometer SmartLab (9kW Rigaku Corporation, Japan), with a scanning angle of 5-70°, a step size of 0.02, and a scanning rate of 10° / min.
[0115] The XRD patterns of the fluorinated gypsum products of Comparative Example 1, Comparative Example 2 and Example 5 are as follows: Figure 7-9 As shown. Figure 7 It can be seen that the anhydrous gypsum in Comparative Example 1 hydrates very slowly, and only a very small amount of dihydrate gypsum is generated; Figure 8 It can be seen that the anhydrous gypsum in Comparative Example 2 hydrates slowly, and only a small amount of dihydrate gypsum is generated, indicating that calcium oxide has a weak effect on hydration; Fig. 9 It can be seen that the anhydrous gypsum in Example 5 hydrates rapidly and a large amount of dihydrate gypsum is generated, indicating that the hydration of sodium molybdate dihydrate is obvious. At the same time, a small amount of insoluble calcium molybdate is generated, indicating that part of the sodium molybdate dihydrate reacts with the fluorinated gypsum component to generate calcium molybdate, making the structure more compact (combined with Fig.12 observe).
[0116] 4. Scanning electron microscope observation: After the physical strength test of the test block (cured for 7 days after demolding), take a thin slice from the broken block (length and width not exceeding 1 cm × 1 cm, thickness not exceeding 2 mm, double-sided flat, able to stick to the conductive silicone), dry the thin slice in a vacuum drying oven at 45 ° C until it reaches a constant weight, and then spray gold. Use a scanning electron microscope Merlin Compact (Zeiss Optical Co., Ltd., Germany) to analyze its morphology, and use the same magnification to observe the thin slice sample.
[0117] The SEM images of the fluorinated gypsum products of Comparative Example 1, Comparative Example 2 and Example 5 are as follows: Figure 10-12 As shown. Fig.10 It can be seen that the microscopic morphology of the fluorinated gypsum product of Comparative Example 1 is "a plate of loose sand" and dispersed particles; Fig.11It can be seen that the microscopic morphology of the fluorinated gypsum product of Comparative Example 2 is mainly granular, with only a small amount of block structure generated, indicating that calcium oxide cannot control the crystal growth well; Fig.12 It can be seen that the morphology of the fluorgypsum product of Example 5 is a prismatic structure, and the layered stacking forms a hard structure, which shows that sodium molybdate dihydrate controls the crystal form of gypsum during the transformation of fluorgypsum from anhydrous gypsum to dihydrate gypsum, from dispersed granular to tightly interwoven prisms.
[0118] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for improving the activity of fluorgypsum, characterized in that: The steps include: (1) mixing fluorgypsum powder, water and calcium oxide uniformly to obtain fluorgypsum slurry; (2) adding sodium molybdate dihydrate to the fluorgypsum slurry and mixing them evenly to obtain a fluorgypsum slurry; (3) Curing the fluorgypsum slurry to obtain a fluorgypsum product.
2. The method for improving the activity of fluorgypsum according to claim 1, characterized in that: In step (1), the mass ratio of the fluorsulphite powder to calcium oxide is (96-104):(0.5-1.5), and the mass ratio of the water to the fluorsulphite powder is (0.29-0.33):1; In step (2), the mass ratio of sodium molybdate dihydrate to fluorite powder is 0.06%-1.5%.
3. The method for improving the activity of fluorgypsum according to claim 2, characterized in that: In step (2), the mass ratio of sodium molybdate dihydrate to fluorite powder is 0.3%-1.1%.
4. The method for improving the activity of fluorgypsum according to claim 1, characterized in that: After obtaining the fluorgypsum slurry, let it stand for 5-10 minutes, and then add the sodium molybdate dihydrate.
5. The method for improving the activity of fluorgypsum according to claim 1, characterized in that: The fluorspar powder is obtained by drying and grinding fluorspar, and the fluorspar powder can pass through a 30-mesh sieve.
6. The method for improving the activity of fluorgypsum according to claim 5, characterized in that: The drying temperature is 45-60° C. and the drying time is 10-24 hours.
7. The method for improving the activity of fluorgypsum according to claim 1, characterized in that: Step (3) includes: A. forming the fluorgypsum slurry in a mold and demoulding; B. After demoulding, continue curing to obtain the fluorgypsum product.
8. The method for improving the activity of fluorgypsum according to claim 7, characterized in that: In step A, the fluorinated gypsum slurry is placed in a mold, compacted, and vibrated on a vibration table. After the fluorinated gypsum slurry is initially solidified, a plastic wrap is applied, and the mold is removed after curing for 10-24 hours.
9. The method for improving the activity of fluorgypsum according to claim 8, characterized in that: The curing in step A and / or B is carried out in a constant temperature and humidity environment, with a temperature of 17-25° C. and a humidity of 60%-70% RH.
10. A fluorgypsum product, characterized in that: The fluorgypsum product is prepared by the method according to any one of claims 1 to 9.
